Evaluation of oral supplementation of free and nanoencapsulated Minthostachys verticillata essential oil on immunological, biochemical and antioxidants parameters and gut microbiota in weaned piglets - Montironi, Ivana D.; Arsaute, Sofía; Roma, Dardo Andrés; Cecchini, María Eugenia; Pinotti, Agustina; Mañas, Fernando; Bessone, Fernando Aníbal; Moreno de LeBlanc, Alejandra de; Alustiza, Fabrisio Eduardo; Bellingeri, Romina; Cariddi, Laura Noelia (Springer, 2024)
Early weaning is an important stressor that impairs the piglet´s health, and essential oils appear as promising candidates to improve it instead of antibiotics. The aim of this study was to evaluate the effect of oral supplementation of free and nanoencapsulated Minthostachys verticillata essential oil (EO and NEO, respectively) on immunological, biochemical and antioxidants parameters as well as on gut microbiota in weaned piglets. EO was extracted by hydrodistillation and nanoencapsulation was performed by high-energy method using Tween 80 and Span 60 as surfactants. EO and NEO were chemically analyzed by gas chromatography-mass spectrometry (GC-MS). The cytotoxic effects of both EO and NEO was evaluated on Caco-2 cell line. For in vivo assay, male weaned piglets (age: 28 days, mean initial body weight: 11.63 ± 0.37 kg) were randomly distributed in six groups of six animals each (n = 6) and received orally EO (10.0 mg/kg/day) or NEO (2.5, 5.0 and 10.0 mg/kg/day), named hereinafter as EO-10, NEO-2.5, NEO-5 and NEO-10, for 30 consecutive days. Animals not treated or treated with surfactants mixture were evaluated as control and vehicle control. Subsequently, histological, hematological and biochemical parameters, cytokines production, oxidative markers, CD4+/CD8+ T cells and gut microbiota were evaluated. GC-MS analysis was similar in both EO and NEO. The NEO was more toxic on Caco-2 cells than EO. Oral supplementation of EO-10 or NEO-10 improved growth performance compared to control group NEO-2.5 or NEO-5 (p < 0.05) groups. NEO-2.5, NEO-5 and NEO-10 did not alter the morpho-physiology of digestive organs and decreased malondialdehyde (MDA) levels in liver compared to control (p < 0.05) or EO-10 groups (p < 0.05, p < 0.01). In addition, NEO-10 showed an increase in CD4+/CD8+ T cells ratio (p < 0.001), and induced the highest serum levels of IL-10 (p < 0.01). Serum triglycerides levels were significantly lower in animals treated with EO-10 or NEO-2.5, NEO-5 and NEO-10 compared to control group (p < 0.001). Gut microbiota analysis showed that NEO-10 favor the development of beneficial intestinal microorganisms to improve parameters related to early weaning of piglets. In conclusion, EO and NEO improved parameters altered by early weaning in piglets however, NEO was safer and powerful. Therefore, NEO should be further studied to be applied in swine health.